HOW EDUCATION FUNDING MANAGEMENT CAN INCREASE THE QUALITY OF EDUCATION IN VOCATIONAL HIGH SCHOOLS? - Nurlatifah, Siti; kurniady, Dedy Achmad (EARR (Educational Administration Research and Review), 2019)
The general objective of this research is to support and analyze the management of educational funding in Vocational High Schools (SMK) in Bandung. The specific objectives in this study, namely: 1) To identify the management of educational funding at SMK in Bandung, 2) To identify the quality of SMK in the city of Bandung, and 3) To find out the role of financial management in improving the quality of education in SMK. This study is descriptive with a quantitative approach. The data source is taken from 32 school principals. The results showed that the management of educational funding had a positive and significant effect on school quality that was equal to 58.7%. The regression equation that is obtained linearly means that the higher the management of education funding, the higher the quality of schools in Vocational High Schools in Bandung.